The Students’ ICT Skills in Producing Infographic Media and Video: Guidance and Counselling E-Project Tasks - Kurniawan, Dydik; Wahyuningsih , Tri (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2022)
The study sees, there is still a lack of student ICT skills in producing a multimedia platform to support guidance and counselling services. This mixed method aimed to analyze the ICT skills of students from the department dept. of Guidance and Counselling in producing interesting, effective, and efficient infographic media and video as well as evaluation materials for lecturers in correcting the shortcomings of the lecture process. Using saturated total sampling technique of 76 students’ from class of 2020 this present study focuses on Infographic Design, Video, and Material. Data collection were based in the form of documentation include e-infographic project tasks, video tasks, infographic assessment sheets, and video assessment sheets which analyzed using descriptive statistics in the form of average values and percentages, which are then converted to qualitative data. The results of the assessment obtained for infographic design (3.53 ), materials in the appropriate category (3.78), and for video (4.00). Media that has been created by students in the form of Infographics and videos provides one of the solutions in providing guidance and counselling services during the Covid-19 pandemic or in the new normal situation. Therefore this study highlighted the excellence in-making skills of students or candidates for Guidance and counseling of Mulawarman University in creating infographic media and videos are very important in supporting and providing guidance and counselling services as their career path in the future.